Rhinoviruses: Colds - Peltola Ville; Jartti Tuomas; Susi Petri (Springer, 2025)
Rhinoviruses belong to a large group of RNAviruses that include 169 virus types classified in three species, A, B, and C, in the Picornaviridae family and the Enterovirus genus. Rhinoviruses replicate in the nasopharynx and the resulting infections maybe asymptomatic or symptomatic with respiratory symptoms. Immunity is type specific, which is why repeated infections caused by different rhinovirus types are common. Rhinovirus infections are extremely frequent. Typical epidemiological feature of rhinoviruses is that several virus types circulate at the same time. Peak season in the Northern Hemisphere is the fall, and a smaller peak is seen in the spring, but in general rhinoviruses are present yeararound. The major transmission routes are droplet transmission and contact transmission directly via hands or indirectly via surfaces and fomites. The most frequent clinical manifestation of rhinovirus is the common cold. Rhinoviruses are also a major cause of lower respiratory tract infections, which often manifest as wheezing illnesses, in young children as bronchiolitis, and in older children and adults as exacerbation of asthma. Rhinoviruses are an important cause of pneumonia and acute otitis media, alone or together with bacteria. The molecular detection of rhinoviruses typically involves reverse transcription quantitative polymerase chain reaction (RT-qPCR) followed by sequencing of partial capsid region to determine the virus type. No antiviral drugs or vaccines against rhinovirus are available. Hygiene precautions and avoidance of contacts are used in prevention.
Viral Infections of Humans: Epidemiology and Control